Pengaruh Kebijakan Dividen Kebijakan Hutang dan Profitabilitas Terhadap Nilai Perusahaan - Oktani, Nurdiah; Benarda (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
This research aims to determine the influence of Dividend Policy, Debt Policy and Profitability on Company Value. This type of research is quantitative research. The population in this research are primary consumer goods sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The number of samples in this research was 23 companies obtained using the purposive sampling method, so that 138 observation data were obtained. The type of data in this research is secondary data obtained in financial reports. The analysis technique used is panel data regression analysis with a significance level of 5%. This research was processed using Evies 9 software. The results of this research simultaneously show that Dividend Policy, Debt Policy and Profitability simultaneously influence company value. Partially, Dividend Policy and Debt Policy have no effect on net profit and Profitability has an effect on company value.